Efisiensi dan Risiko Usahatani Bawang Merah di Kecamatan Gebang, Kabupaten Cirebon, Jawa Barat (Jurnal Agribisnis Indonesia, 2023)
This study aims to determine the efficiency and risk in shallot farming in Gebang District, Cirebon Regency, West Java. The research method used was a survey method of 44 shallot farmers selected purposively. Data analysis used includes: (1) Descriptive Analysis, (2) Cobb-Douglas Production Function with the SFA approach using Frontier 4.1, (3) Coefficient of Diversity, and (4) Coefficient of Risk Aversion. The results show that  factors influencing shallot production were land area, seeds, SP-36 fertilizer, KCl fertilizer and labor. Farmers in their farming activities have achieved a good level of technical, allocative and economic efficiency. The aspect of technical efficiency, farmers have been able to achieve maximum output from a given set of input and from the aspect of allocative efficiency farmers have been able to use optimum inputs to produce a certain amount of output. Technical inefficiency is influenced by age, length of formal education, length of business and the number of farmer family members. Shallot farmers in the Gebang subdistrict, Cirebon, in running their farming business do not think about production risk and income risk.